2015
DOI: 10.1016/j.envres.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Children's personal exposure to air pollution in rural villages in Bhutan

Abstract: Exposure assessment studies conducted in developing countries have been based on fixed-site monitoring to date. This is a major deficiency, leading to errors in estimating the actual exposures, which are a function of time spent and pollutant concentrations in different microenvironments. This study quantified school children's daily personal exposure to ultrafine particles (UFP) using real-time monitoring, as well as volatile organic compounds (VOCs) and NO2 using passive sampling in rural Bhutan in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…The measuring periods in most of the studies were 24 or 48 hours . Conversely, the analysis periods of Wangchuk et al (2015), Leaffer et al, and both studies carried out by Dirks et al were shorter: 8 hours on three consecutive days, 3 hours during seven winter days and seven summer days, and only the time during transportation to school, respectively (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The measuring periods in most of the studies were 24 or 48 hours . Conversely, the analysis periods of Wangchuk et al (2015), Leaffer et al, and both studies carried out by Dirks et al were shorter: 8 hours on three consecutive days, 3 hours during seven winter days and seven summer days, and only the time during transportation to school, respectively (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…Of the 32 articles that fulfilled our criteria, 22 quantified UFP levels in children's specific microenvironments (Table ; Figure and ), while the other 10 studies that were selected measured children's personal exposure to UFP by means of active samplers carried by children (Table ; Figure ). Among the studies regarding microenvironment exposures, 18 (82%) referred to UFP levels in schools or nurseries, 3 referred to transport (2 to schools and 1 to baby prams), 1 considered the UFP levels in heavily trafficked streets, and 2 measured levels in homes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistently, other research groups (Park and Ikeda, 2006;Tuomainen et al, 2003) observed that certain VOC indoor concent -rations decreased gradually over 3-y follow-up periods. In addition, a great deal of research groups reported that indoor VOC concentrations were typically higher than outdoor VOC concentrations in residential, school, hair salon, and office buildings (Cometto-Muñiz and Abraham, 2015;de Gennaro et al, 2014;Do et al, 2015;Gokhale et al, 2008;Mishra et al, 2015;Su et al, 2013;Uchiyama et al, 2015;Wangchuk et al, 2015). Table 3 reveals the emission rates of 9 selected VOCs (2E1H, EOL, 1POL, 2POL, DCA, NNA, ACT, 2BT, and 4M2P) estimated for the investigated apartments according to survey period.…”
Section: Temporal Characteristics Of Selected Vocsmentioning
confidence: 99%